2000
DOI: 10.1038/sj.gt.3301284
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transfer of human hepatocyte growth factor gene accelerates re-endothelialization and inhibits neointimal formation after balloon injury in rat model

Abstract: Although most therapeutic strategies to prevent restenosis are designed to inhibit vascular smooth muscle cell (VSMC) proliferation directly, VSMC proliferation might be indirectly inhibited by re-endothelialization, as endothelial cells secrete antiproliferative and antithrombotic substances. We hypothesized that application of an endothelium-specific growth factor to balloon-injured arteries could accelerate re-endothelialization, thereby attenuating intimal hyperplasia. In this study, we investigated in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 41 publications
5
67
0
1
Order By: Relevance
“…Since recent studies demonstrated the therapeutic efficacy of re-endothelialization using endothelium-specific growth factors, such as VEGF (vascular endothelial growth factor) or HGF (hepatocyte growth factor), 12,13 it is noteworthy to examine the effects of E2F decoy ODN on endothelial function. Thus, we measured the vasomotor response to an endothelium-dependent agonist.…”
Section: Efficacy Of E2f Decoy Strategy For Prevention Of Neointimal mentioning
confidence: 99%
“…Since recent studies demonstrated the therapeutic efficacy of re-endothelialization using endothelium-specific growth factors, such as VEGF (vascular endothelial growth factor) or HGF (hepatocyte growth factor), 12,13 it is noteworthy to examine the effects of E2F decoy ODN on endothelial function. Thus, we measured the vasomotor response to an endothelium-dependent agonist.…”
Section: Efficacy Of E2f Decoy Strategy For Prevention Of Neointimal mentioning
confidence: 99%
“…Indeed, overexpression of human HGF vector in rat ballooninjured vessels resulted in a significant increase in reendothelialized area as assessed by Evans' blue dye staining. 20 If so, enhanced reendothelialization by increased vascular HGF would result in restoration of anatomical integrity and recovery of physiological function. Therefore, we examined vasomotor response to an endothelium-dependent agonist.…”
Section: Matsumoto Et Al Downregulation Of Vascular Hgf By Angiotensimentioning
confidence: 99%
“…25 Moreover, our previous report demonstrated that the area covered by endothelial cells in rat balloon-injured vessels was significantly increased by in vivo transfer of the HGF gene. 26 We also demonstrated that Effect of nifedipine on endothelial function in smokers K Yamasaki et al administration of cilostazol improved endotheliumdependent vascular relaxation through induction of serum HGF in rat balloon-injured vessels. 27 These data, including the present findings, are consistent with our previous in vitro findings that the downregulation of HGF is caused by downregulated c-AMP and/or upregulated TGF-b in a hypoxic or high glucose condition which promotes atherosclerosis, and addition of HGF could rescue endothelial cells from death.…”
Section: Discussionmentioning
confidence: 54%